Functional brain changes using electroencephalography after a 24-week multidomain intervention program to prevent dementia - Park, Hee Kyung; Choi, Seong Hye; Kim, SeonMyeong; Park, Ukeob; Kang, Seung Wan; Jeong, Jee Hyang; Moon, So Young; Hong, Chang Hyung; Song, Hong-Sun; Chun, Buong-O; Lee, Sun Min; Choi, Muncheong; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Quantitative electroencephalography (QEEG) has proven useful in predicting the response to various treatments, but, until now, no study has investigated changes in functional connectivity using QEEG following a lifestyle intervention program. Purpose: We aimed to investigate neurophysiological changes after a 24-week multidomain intervention program, the SoUth Korean study to PrEvent cognitive impairment and protect BRAIN health through lifestyle intervention in an at-risk older adults (SUPERBRAIN) study, using quantitative electroencephalography (QEEG). Methods: Subjects (n = 127) with at least one risk factor for dementia were randomized into facility-based intervention group (n = 44), home-based intervention group (n = 49), and control group (n = 34). The spectrum power and power ratio of EEG were calculated. Source cortical current density and functional connectivity were estimated by standardized low-resolution brain electromagnetic tomography. Results: Both of the intervention groups showed increases in the relative power of the beta1 band and in the imaginary part of coherence (iCoh) of the alpha band compared with the controls. Decreases in the characteristic path lengths in the left temporal cortex and right anterior cingulate cortex were observed in the intervention groups. Conclusion: We successfully showed positive biological changes, including increased functional connectivity and higher global efficiency on QEEG after a multidomain intervention program. Further studies with larger sample sizes are needed to confirm changes in functional connectivity through a multidomain intervention program.